Reshaping HRD in Light of the COVID-19 Pandemic: An Ethics of Care Approach. Issue 1 (February 2021) - McGuire, David; Germain, Marie-Line; Reynolds, Kae
The Problem: The COVID-19 pandemic has shone a stark light on workplace inequities and injustices. Aside from disrupting daily routines and ways of working, the pandemic has unmasked significant and troubling differences in the treatment and status of productive and reproductive labor. As we recover from the pandemic, how can workplaces properly recognize and value the contribution of reproductive labor? The Recommendation: We focus on ethics of care as a foundational aspect of learning and human development. Care is proximal and contextual and expressions of care require managers and HRD professionals to engage with and address employees' needs in a way that recognizes the complexity of individual situations. This may lead to the transformation of work and workplaces and bring employees into a more participatory, inclusive and democratic relationship with employers. We offer four suggestions for how HRD practitioners can practically embed an ethics of care approach within organizations. The Stakeholders: This article is relevant to human resource development (HRD) scholars and practitioners who are interested in building sustainable, caring and healthy workplaces in a post-pandemic world.